PERENNIAL AND ANNUAL DROUGHT- AND SALT-RESISTANT FORAGE PLANTS IN THE VAVILOV COLLECTION - N. I. Dzyubenko; A. V. Bukhteeva; A. A. Kochegina (Труды по прикладной ботанике, генетике и селекции)
The 100-year history of building up the VIR collection of genetic resources of drought- and salt-resistant perennial and annual forage crops and its current status are described. Numerous expeditions were conducted to collect valuable germplasm material. The collections of a number of drought- and salt-resistant forage plants were established and studied. Breeders from VIR, its network and other breeding centers developed drought-resistant and salt-resistance varieties on the basis of the Vavilov collection. Theoretical and practical research on the physiology of desert plants was further developed. Currently salt tolerance of forage crops is assessed using molecular methods.